Impact of Antibodies That React With Liver Tissue and Donor-Specific Anti-HLA Antibodies in Pediatric Idiopathic Posttransplantation Hepatitis. Issue 5 (May 2017) - Hirata, Yoshihiro; Yoshizawa, Atsushi; Egawa, Hiroto; Ueda, Daisuke; Okamoto, Shinya; Okajima, Hideaki; Yurugi, Kimiko; Hishida, Rie; Hirai, Hideyo; Miyagawa-Hayashino, Aya; Maekawa, Taira; Haga, Hironori; et al.
Abstract : Background: The cause of late graft dysfunction has not been elucidated. Although an antibody-mediated reaction is suspected as a potential mechanism, the target antigens have not been clarified. Methods: To clarify the etiology of idiopathic posttransplantation hepatitis (IPTH), we simultaneously examined the presence of antibodies that react with liver tissue (ARLT) by means of indirect immunofluorescence staining, as well as the presence of donor-specific anti-human leukocyte antigen antibodies (HLA-DSA). A subanalysis of the IPTH group was also performed. Within the IPTH group, the correlation between ARLT titer and clinical data were analyzed. Results: In the sera of patients with IPTH (30 patients), ARLT were found at a significantly higher frequency than in patients without IPTH (42 patients; P < 0.001). Moreover, the ARLT titer appeared to be correlated with the severity of hepatitis or hepatic injury. In contrast, the frequency of HLA-DSA was significantly lower in patients with IPTH than in patients without IPTH ( P = 0.001). Conclusion: Our findings indicate that ARLT, and not HLA-DSA, profoundly influence the etiology of IPTH. Abstract : The authors show that antibodies that react with liver tissue and not donor-specific anti-human leukocyte antigen antibodies, profoundly influence the etiology of idiopathic posttransplantation hepatitis in children providing a rationale for therapy.